2015
DOI: 10.1111/1346-8138.13218
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, muscular and metabolic characteristics in patients with neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 (NF1) has many reported clinical characteristics. We previously found that NF1 patients (especially men) had lower body mass index (BMI) than controls, but the reason has not been elucidated. To address this issue, a retrospectively case-control study was conducted. Anthropometric and serum chemistry data that potentially relate to BMI were collected from medical records of NF1 patients and their age- and sex-matched controls. Enrollment of 98 adult patients who underwent skin surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Probably, men and women are affected by NF1 in different ways in their body compartments, which can be related to situations like AMB greater in men and/or fat accumulation greater in women. Other studies 28,29 have also found differences between men and women for variables such as BMI, reinforcing the need to assess the impact of NF1 in each sex.…”
Section: Discussionmentioning
confidence: 96%
“…Probably, men and women are affected by NF1 in different ways in their body compartments, which can be related to situations like AMB greater in men and/or fat accumulation greater in women. Other studies 28,29 have also found differences between men and women for variables such as BMI, reinforcing the need to assess the impact of NF1 in each sex.…”
Section: Discussionmentioning
confidence: 96%
“…NF1 has 40 been associated with short stature, as well as reduced body mass index in males (Koga et al,41 2016; Souza et al, 2016), although the mechanisms underlying these manifestations are 42 unknown. Alterations in certain metabolites have been reported in NF1 patients, though these 43 are sex-specific (Koga et al, 2016). The incidence of diabetes mellitus, deaths from diabetes 44 mellitus, and fasting blood glucose levels are lower in individuals with NF1 than in healthy 45 controls (Martins et al, 2016).…”
Section: Introduction 22mentioning
confidence: 98%
“…Thus, this experiment demonstrated that 285 catalytic activity from the GRD itself was critical for dNf1 modulation of metabolic rate, rather Alterations in specific metabolites have been reported, though these are sex-specific (Koga et 301 al., 2016). Diabetes mellitus -as well as deaths from noted diabetes complications -is rare in 302 patients with NF1 (Koga et al, 2016). Loss of NF1 increases glycolysis and decreases 303 respiration via mitochondrial ERK signaling, which may play a role in tumor growth (Masgras et 304 al., 2017).…”
mentioning
confidence: 99%
“…There was no evidence of infection or cardiovascular dysfunction that could explain the acute death. Recent studies show that NF1 patients have a high prevalence of being underweight with short stature accompanied by lower BMI (32)(33)(34). Further studies need to be conducted to assess body composition within NF1 patients that could be underweight due to a decrease in body fat and a similar underlying metabolic condition as compared to this systemic knockout Nf1 model.…”
Section: Discussionmentioning
confidence: 99%